Comparative Ecocriticism The Bajo Tribe Southeast Sulawesi To Movie Script Avatar: The Way Of Water 2022: - Rumra, Muh. Zulfikar Givari; Moelier, Dahlia D.; Wahyuni, Rezki Amalia (Humaniora: Journal of Linguistics, Literature, and Education, 2024)
This research aims to compare the environmental issues and the relationship between humans and nature in the Bajo tribe of Southeast Sulawesi, Indonesia, with those depicted in the movie script Avatar: The Way of Water by James Cameron. In analyzing the data, the researcher used qualitative descriptive method. The data were obtained by using reading, note- taking, analyzing techniques through an ecocriticism approach to literary works and to classify the types that contained in the movie script, the writer used theory of Greg Garrad. This research employs an ecocriticism approach to analyze the environmental issues and ecological interactions in both the Bajo tribe and the movie script. The research objectives include identifying environmental issues in the Bajo tribe and the movie, describing the interrelationship between humans and nature in both contexts. The significance of this study lies in its contribution to enriching the analysis of environmental themes in literary works, particularly in the context of ecocriticism. The findings reveals that both tribes shared narrative of industrial-driven degradation, the prioritization of economics over ecological health, and the vulnerability of indigenous communities.